Proposed reinforcement games in English grade V based in a study and analysis for teaching enrichment exercises - De Leon, Ligaya V. Ferrer 1945- (1973)
The study is an analysis of reinforcement exercises in English (Grade V) in an attempt to construct and propose some reinforcement games for this grade level. From the findings, it is established that there is a need for providing more games as teachers' aids in teaching English grade V. It is concluded that games as an enrichment or reinforcement activity can effectively meet the needs, interests, and abilities of grade V children. Some language games based on the contents of the text used in grade V are devised to reinforce language lessons.